1985
DOI: 10.1002/bjs.1800720218
|View full text |Cite
|
Sign up to set email alerts
|

Vascular occlusion in the pathogenesis of complicated amoebic colitis: Evidence for an hypothesis

Abstract: Amoebic perforation of bowel, the final and most serious manifestation of transmural amoebic colitis, is due to thrombotic occlusion of vessels supplying the segment of bowel with subsequent infarction and ischaemic necrosis. The ischaemic nature of the necrosis is confirmed by its shape and the demonstration of vascular thrombosis in the resected specimens of perforated amoebic colitis. Specimen angiography confirms the avascular area confined to the macroscopic lesions. Thrombotic occlusion and amoebic invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Vascular pathology in amoebic colonic disease has been implicated in the pathogenesis of fulminant transmural colitis and has served as the link between amoebic intestinal and extra-intestinal hepatic involvement [23,29]. It has been stated that vascular changes such as dilatation and congestion are common and that "thrombosis is rare, fibrin deposition and vasculitis are never seen" [4].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular pathology in amoebic colonic disease has been implicated in the pathogenesis of fulminant transmural colitis and has served as the link between amoebic intestinal and extra-intestinal hepatic involvement [23,29]. It has been stated that vascular changes such as dilatation and congestion are common and that "thrombosis is rare, fibrin deposition and vasculitis are never seen" [4].…”
Section: Discussionmentioning
confidence: 99%
“…Toxins present in the organism's microfilament, a membrane phospholipase and a phosphoglutamase, which cause mucosal defects, account for the invasive capacity of E. histolytica. 13,14 It has been suggested that the parasite invades the nutrient arterioles with subsequent occlusion and ischemia of the bowel wall, resulting in progression of the initial superficial ulceration to transmural necrosis and perforation. 15 Grossly, the bowel segments were ulcerated and friable.…”
Section: Discussionmentioning
confidence: 99%
“…However, transmural disease recognised at laparotomy due to omental wrapping of the affected bowel may progress to result in colonic perforation with consequent high mortality. 1 However, amoebiasis involving the ileum is overlooked as it is considered a clinical rarity. In the study of 3013 cases of amoebic dysentery and its complications by Adams and Macleod, 2 not a single case of ileal involvement was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some 10% of the world's population harbour amoebae but only a proportion of this population ever develop symptoms. 1 Colonic amoebiasis infection and its pathology have been well documented. However, amoebic involvement of the small intestine is still considered a rarity.…”
mentioning
confidence: 99%